The role of microbes in the formation of modern and ancient phosphatic mineral deposits - Crosby, Chris H.; Bailey, Jake (Frontiers in Microbiology, 2012)
The formation of marine phosphatic mineral deposits remains incompletely understood, despite decades of research. The involvement of bacteria in this process has long been suspected, and both modern and ancient associations between bacteria and phosphorites have been recorded. Only recently has a specific bacterial metabolic process associated with the formation of phosphorites been discovered. Recent studies demonstrate that polyphosphate utilization by sulfide-oxidizing bacteria results in the rapid precipitation of apatite – providing at least a partial mechanism to explain the close spatial correlation between accumulations of sulfide-oxidizing bacteria and modern phosphorites. Possible fossilized bacteria are known from ancient phosphatic mineral deposits. Potentially, the fossilized cells represent the remains of bacteria that induced the formation of those phosphorites. However, robust criteria for the recognition of these bacteria have yet to be identified.